PENGUATAN NILAI-NILAI KARAKTER PANCASILA MELALUI KEGIATAN KEAGAMAAN DI SMA NEGERI 1 MUARA PADANG BANYUASIN - Fatma, Charninda; Kms. Badaruddin; Fitri Oviyanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to describe and analyze how religious activities are at SMA Negeri 1 Muara Padang Banyuasin what are the supporting and inhibiting factors for strengthening Pancasila character values through religious activities at SMA Negeri 1 Muara Padang Banyuasin and what is the strategy for strengthening Pancasila character values through religious activities at SMA Negeri 1 Muara Padang Banyuasin The type of research used in this research is descriptive qualitative. Data collection techniques in the form of observation, interviews and documentation. The data obtained was then analyzed descriptively using data analysis techniques in the form of data reduction, data presentation, and drawing conclusions. Based on the results of the analysis that the researchers did, it can be concluded that the implementation of religious activities at SMA Negeri 1 Muara Padang Banyuasin, namely, shifting boxes, reading the Qur'an before learning takes place, women's daughters, Ramadhan, and celebrating Islamic holidays such as Maulid Nabi and Isro' Mi 'roj. Supporting factors are in the form of facilities and infrastructure, teacher commitment, and student involvement in the implementation of religious activities. Independent school curriculum, and the spirit of Pancasila students. While the inhibiting factors are the lack of awareness of some students in the implementation of religious activities, the presence of environmental conditions, and the presence of peers who influence them. The strategy to strengthen Pancasila character values is through exemplary and habituation strategies, as well as by inviting the support of community religious committees and leaders.